Building Early Childhood Social Skills Through Learning Empathy Cooperation and Responsibility - Khatijah, Yayak; Windarti, Windarti; Iswatiningsih, Daroe (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
Instilling social skills in early childhood is an important part of character building and healthy social interactions in the future. This article discusses the importance of developing social skills in early childhood through learning about empathy, cooperation, and responsibility. Through the right approach, children can learn to understand the feelings of others, work together in groups, and feel responsible for their own actions. This study began by formulating the objectives and focus of the study, namely to explore how learning empathy, cooperation, and responsibility can build social skills in early childhood. After that, a literature review was conducted to deepen understanding of the theory of child social development and learning methods that can be applied. The subjects of this study were children aged 4-6 years, teachers at ABA 02 Bumiaji Kindergarten, and parents of children. Instilling the values ​​of empathy, cooperation, and responsibility from an early age is expected to form a strong foundation for better social development in children, improve communication skills, and create a more harmonious social environment. Therefore, education that integrates these social skills is very important to equip children with the ability to adapt and contribute positively to society in the future.